Coq3p relevant residues for protein activity and stability. Issue 7 (10th November 2021) - Paulela, Janaina A; Gomes, Fernando; Camandona, Vittoria de Lima; Alegria, Thiago G P; Netto, Luis E S; Bleicher, Lucas; Barros, Mario H; Ferreira-Junior, Jose Ribamar
ABSTRACT: Coenzyme Q (CoQ) is an essential molecule that consists of a highly substituted benzene ring attached to a polyprenyl tail anchored in the inner mitochondrial membrane. CoQ transfers electrons from NADH dehydrogenase and succinate dehydrogenase complexes toward ubiquinol-cytochrome c reductase, and that allows aerobic growth of cells. In Saccharomyces cerevisiae, the synthesis of CoQ depends on fourteen proteins Coq1p-Co11p, Yah1p, Arh1p, and Hfd1p. Some of these proteins are components of CoQ synthome. Using ab initio molecular modeling and site-directed mutagenesis, we identified the functional residues of the O-methyltransferase Coq3p, which depends on S-adenosylmethionine for catalysis and is necessary for two O-methylation steps required for CoQ maturation. Conserved residues as well as those that coevolved in the protein structure were found to have important roles in respiratory growth, CoQ biosynthesis, and also in the stability of CoQ synthome proteins. Finally, a multiple sequence alignment showed that S. cerevisiae Coq3p has a 45 amino acid residues insertion that is poorly conserved or absent in oleaginous yeast, cells that can store up to 20% of their dry weight as lipids. These results point to the Coq3p structural determinants of its biological and catalytic function and could contribute to the development of lipid-producing yeast for biotechnology. Abstract : The authors discuss identification of the functional residues of the O-methyltransferase Coq3p, which is required for biosynthesis of Coenzyme Q and efficient respiratory growth of yeast.